2013
DOI: 10.1161/atvbaha.112.300263
|View full text |Cite
|
Sign up to set email alerts
|

Transintestinal Cholesterol Excretion Is an Active Metabolic Process Modulated by PCSK9 and Statin Involving ABCB1

Abstract: Objective-Transintestinal cholesterol excretion (TICE) is an alternate pathway to hepatobiliary secretion. Our study aimed at identifying molecular mechanisms of TICE. Approach and Results-We studied TICE ex vivo in mouse and human intestinal explants, and in vivo after bile diversion and intestinal cannulation in mice. We provide the first evidence that both low-density lipoprotein (LDL) and high-density lipoprotein deliver cholesterol for TICE in human and mouse jejunal explants at the basolateral side. Prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 40 publications
(54 reference statements)
1
56
0
Order By: Relevance
“…In line with our data, full absence of PCSK9 was recently reported not to be associated with hepatic lipid accumulation or fecal excretion of cholesterol (43). However, contrasting data in PCSK9 −/− mice demonstrated increased LDL-C excretion via the transintestinal cholesterol excretion pathway and subsequently mildly increased fecal neutral sterol loss, with unfortunately no data on fecal bile acid loss (44). As opposed to PCSK9 inhibition by alirocumab in the present study, lack of PCSK9 was reported to increase fecal bile acid output (43).…”
Section: Discussionmentioning
confidence: 99%
“…In line with our data, full absence of PCSK9 was recently reported not to be associated with hepatic lipid accumulation or fecal excretion of cholesterol (43). However, contrasting data in PCSK9 −/− mice demonstrated increased LDL-C excretion via the transintestinal cholesterol excretion pathway and subsequently mildly increased fecal neutral sterol loss, with unfortunately no data on fecal bile acid loss (44). As opposed to PCSK9 inhibition by alirocumab in the present study, lack of PCSK9 was reported to increase fecal bile acid output (43).…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of PCSK9 on RCT may not only be mediated by LDLR lowering in liver. Le May et al [55 ▪▪ ] showed that PCSK9-mediated LDLR degradation in small intestine represses the delivery of LDL-C and HDL-C for trans-intestinal cholesterol excretion, a nonbiliary route of fecal neutral sterol loss that contributes approximately 30% of total sterol excretion in mice, or 60% upon liver X receptor activation [56]. An important future direction is to further delineate the roles of PCSK9 in liver and intestinal mechanisms of RCT.…”
Section: Potential Roles Of Pcsk9 In Reverse Cholesterol Transport Anmentioning
confidence: 99%
“…37 It is interesting to note that fasting HDL particles isolated from ERN/LRPT-treated patients displayed a reduced HDL-CE liver delivery as compared with their equivalent counterparts isolated from patients before ERN/LRPT treatment; however, an equivalent increase in HDL-mediated RCT to feces was observed, thus suggesting that niacin might increase cholesterol elimination via a liver-independent mechanism, such as the transintestinal cholesterol excretion pathway. 38 Human ApoB/CETP double transgenic mice fed with niacin showed significant reduction in P2Y13 gene expression in both the liver and intestine. The niacin-induced reduction in P2Y13 expression in the liver has been previously proposed as potential mechanism underlying HDL-C raising effect of niacin.…”
mentioning
confidence: 99%